Immunotherapy in head and neck cancers: A new challenge for immunologists, pathologists and clinicians. (April 2018) - Outh-Gauer, Sophie; Alt, Marie; Le Tourneau, Christophe; Augustin, Jérémy; Broudin, Chloé; Gasne, Cassandre; Denize, Thomas; Mirghani, Haitham; Fabre, Elizabeth; Ménard, Madeleine; Scotte, Florian; Tartour, Eric; et al.
Highlights: Immunotherapy revolution aims to reverse the microenvironment anergy. Clinical trials are currently ongoing in head and neck cancer patients. Viral infection (HPV, EBV) induces changes in the microenvironment. Reliable biomarkers are needed for patient stratification and treatment selection. IFNγ, MHC molecules, CD8+ T cell density may be predictive of therapeutic response. Abstract: Cancer occurrence can be understood as the result of dysfunctions in immune tumoral microenvironment. Here we review the recent understandings of those microenvironment changes, regarding their causes and prognostic significance in head and neck (HN) carcinoma. We will focus on HN squamous cell cancer (SCC) and nasopharyngeal carcinomas (NPC). Their overall poor prognosis may be improved with immunotherapy in a subset of patients, as supported by current clinical trials. However, finding reliable markers of therapeutic response is crucial for patient selection, due to potential severe adverse reactions and high costs. Half of HNSCC exhibit PD-L1 expression, this expression being higher in HPV-positive tumors. In recent clinical trials, a better therapeutic response to anti-PD-1 was obtained in patients with higher PD-L1 expression. The Food and Drug Administration (FDA) approved the use of these therapeutics without stating a need for patient selection regarding PD-L1 status. Activation status, density and localization of TIL as well as PD-L2, γ-interferon, inflammatory cytokines, epithelial-mesenchymal transition phenotype and mutational burden may all be potential therapeutic response markers. In Epstein-Barr Virus (EBV)-induced nasopharyngeal non-keratinizing cancer, PD-L1 is over-expressed compared to EBV-negative tumors. A 22% response rate has been observed under anti-PD-1 treatment among PD-L1-positive NPC patients. A better understanding of immune checkpoint regulation processes may allow patients to benefit from these promising immunotherapies.